The Effect of Imagery on Reducing Anxiety and Improving Concentration in Gymnastics Performance - Joan Rafael Thenu; Yusuf Hidayat; Helmy Firmansyah (Indonesian Journal of Sport Management, 2025)
This study aims to examine the effect of mental imagery training on anxiety reduction, concentration improvement, and performance enhancement among gymnastic athletes. The research employed a quasi-experimental design with a pretest–posttest control group, involving 26 active gymnasts from Bandung City, divided equally into an experimental and a control group. The experimental group underwent 16 sessions of structured mental imagery intervention, while the control group continued with routine training. Data were collected using the Hamilton Anxiety Rating Scale (HARS), Grid Concentration Test (GCT), and Test of Performance Strategies (TOPS), then analyzed using the Shapiro–Wilk test, Levene’s test, and independent sample t-test at a 0.05 significance level. The results revealed significant differences between the experimental and control groups in all measured variables: anxiety (t = -10.676; p < 0.001), performance (t = 5.377; p < 0.001), and concentration (t = 2.513; p = 0.019). These findings indicate that mental imagery effectively decreases competitive anxiety, enhances attentional focus, and improves overall performance in gymnastic routines. The positive effects can be explained through neural and psychological mechanisms—mental imagery activates motor representations in the brain similar to real movement, reinforcing neuromuscular pathways and cognitive readiness. This process enhances motor coordination and emotional control, essential for complex sports like gymnastics that require high precision, rhythm, and composure. However, the benefits of imagery may vary depending on individual vividness, frequency, and quality of mental practice. In conclusion, mental imagery training is a scientifically supported psychological intervention that can complement physical training programs to optimize gymnastic performance. Coaches and sport psychologists are encouraged to integrate structured and guided imagery sessions into regular training to foster both physical and mental readiness.